Improving Power Quality with the Use of a New Method of Serial Active Power Filter (SAPF) Control - Hrbac, Roman; Mlcak, Tomas; Kolar, Vaclav (Elektronika ir Elektrotechnika, 2017)
The quality of electric energy has currently become a widely discussed issue. The operation of appliances with nonlinear power consumption and with harmonic distorted current leads to voltage drops on network impedance, which in turn leads to power voltage distortion. To transform the distorted network voltage into harmonic voltage and thus improve the quality of electric energy, it is possible to use serial active power filters. SAPF can also be used as line conditioners. These devices are able to regulate supply voltage at the ends of a distribution grid, so that it meets the relevant standards. Line conditioners are also used in the increasingly widespread off grid systems. This paper deals with serial active power filter control. A new control method, called “comparative method”, is presented. The efficiency of this method is demonstrated by measurement results, and compared with standard methods of active power filter control, such as the Butterworth filter method, or the Fast Fourier Transform based method. DOI: http://dx.doi.org/10.5755/j01.eie.23.1.17578